Chitosan-P407-PNIPAM hydrogel loaded with AgNPs/lipid complex for antibacterial, inflammation regulation and alveolar bone regeneration in periodontitis treatment - Zhang, Chengdong; Fei, Yachen; Li, Meng; Li, Jing; Tang, Maomao; Wang, Guichun; Li, Jiaxin; Wang, Yuxiao; Ding, Yang; Peng, Chengjun; Li, Mengjie; Gui, Shuangying; et al. (International journal of biological macromolecules, 2025)
Periodontitis is an oral chronic inflammatory disease induced by pathogenic bacteria. Pathogens continuously activate immune cells to express a large number of pro-inflammatory factors and reactive oxygen species, eventually leading to periodontal tissue damage. Poor eradication of pathogenic bacteria, persistent inflammatory response and impaired periodontal tissue regeneration are the main challenges to control the progression of periodontitis. However, current clinical drug treatment fails to comprehensively address these issues. In this paper, a chitosan-P407-PNIPAM scaffold multi-crosslinked hydrogel (A/CQ-ML@Gel) encapsulating AgNPs and lipid complex (CQ-ML) is developed. This hydrogel shows thermo- and pH-sensitive properties, exhibits excellent injectability, high viscosity and reliable post-injection mechanical strength. A/CQ-ML@Gel possesses a significant antibacterial effect to Porphyromonas gingivalis after implantation, and then by virtue of the programmed release of quercetin microemulsion and caffeic acid phenethyl ester in CQ-ML, exerting excellent inflammation regulation and osteogenic differentiation of periodontal ligament stem cells. Notably, A/CQ-ML@Gel could activate mitophagy through PINK1/Parkin in inflammatory macrophages, thereby inhibiting the production of excess reactive oxygen species, ultimately reprogramming M1/M2 macrophages phenotype for inflammation suppression. In summary, we present an innovative insight into periodontal delivery system for trimodal synergistic therapy strategy in periodontitis.